Multiprofessional team and sports practice by people with disabilities (Research, Society and Development, 2022)
Introduction: the practice of physical activities is related to a better quality of life. In the case of people with disabilities, sport can assist in their rehabilitation process. The work analyzed the perception of the multiprofessional team about the strategy of attendance, social interaction and mental health of disabled sports practitioners. Method: a qualitative, descriptive and transversal approach was used, based on a field study, with a convenience sample of 10 professionals. Results: four categories were identified: service strategies; perceptions about the rehabilitation process; social and family support and understanding of mental health. Discussion: the work of the multiprofessional team is based on welcoming, evaluation and counseling, which contributes to the patient's biopsychosocial development. In addition, the sport proved to be a widely accepted resource for the team. Conclusion: it is noticed that there is a need for public incentive, professional qualification and understanding of the disabled body.